Opening the University to Virtual Training Spaces: A Challenge to Student Autonomy - Thierry Karsenti; François Larose; Mauricio Núñez (Universidad Autónoma de Baja California, 2002)
The objective of this article is to present the achievements and problems experienced by a group of 140 pedagogy students through the implementation of a course given on the Internet. The data comes from the analysis (of the content) of interviews conducted with several students, as well as of the electronic messages received (n=1614) and of the transcripts of conversations (on line) in real time (chat). The results awaken our interest as they reflect the importance of rigorous pedagogical management, that is, of courses which take into account the specific educational criteria in their production, and particularly in relation to courses taught using the Internet. The results of this analyses will facilitate the choice of more efficient ways of designing virtual courses. We hope that what we have found through this experience may inspire teachers in such production, and that it may contribute to stimulating reflection on the problems which must be avoided from a critical point of view.